First Report of the Biosynthesis and Characterization of Silver Nanoparticles Using Scabiosa atropurpurea subsp. maritima Fruit Extracts and Their Antioxidant, Antimicrobial and Cytotoxic Properties - Badiaa Essghaier; Nourchéne Toukabri; Rihab Dridi; Hédia Hannachi; Inès Limam; Filomena Mottola; Mourad Mokni; Mohamed Faouzi Zid; Lucia Rocco; Mohamed Abdelkarim (Nanomaterials, 2022)
Candida and dermatophyte infections are difficult to treat due to increasing antifungal drugs resistance such as fluconazole, as well as the emergence of multi-resistance in clinical bacteria. Here, we first synthesized silver nanoparticles using aqueous fruit extracts from Scabiosa atropurpurea subsp. maritima (L.). The characterization of the AgNPs by means of UV, XRD, FTIR, and TEM showed that the AgNPs had a uniform spherical shape with average sizes of 40–50 nm. The biosynthesized AgNPs showed high antioxidant activity when investigated using 1,1-diphenyl-2-picryl-hydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. The AgNPs displayed strong antibacterial potential expressed by the maximum zone inhibition and the lowest MIC and MBC values. The AgNPs revealed a significant antifungal effect against the growth and biofilm of Candida species. In fact, the AgNPs were efficient against Trichophyton rubrum, Trichophyton interdigitale, and Microsporum canis. The antifungal mechanisms of action of the AgNPs seem to be due to the disruption of membrane integrity and a reduction in virulence factors (biofilm and hyphae formation and a reduction in germination). Finally, the silver nanoparticles also showed important cytotoxic activity against the human multiple myeloma U266 cell line and the human breast cancer cell line MDA-MB-231. Therefore, we describe new silver nanoparticles with promising biomedical application in the development of novel antimicrobial and anticancer agents.